1995
DOI: 10.1111/j.1365-2028.1995.tb00798.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet, seasonal abundance and microhabitats of Praomys (Mastomys) natalensis (Rodentia: Muridae) and other small rodents in a Kenyan sub‐humid grassland community

Abstract: The diet, seasonal abundance and microhabitats of Praomys natalensis, Tatera robusta, Mus minutoides and M. triton, live-trapped on a five ha grid over an eight-month period, were studied in a dry sub-humid grassland in Kahawa, Kenya.All the species were found to be omnivorous, feeding mainly on seeds and arthropods, with herbage forming a small but regular part of their diet. The diet of Praomys, though similar to that of M. minutoides, was significantly (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
5
11
0
Order By: Relevance
“…For rodent communities in general, vegetation cover and related productivity seem to be the main environmental determinants of community composition (Bian et al, 1994;Adler, 1995;Oguge, 1995). In the present study and other desert systems (south Bukhara desert, Uzbekistan, Shenbrot, 1992; Asian deserts, Shenbrot et al, 1994;Anix desert, China, Liu et al, 1994;Negev highlands, Israel, Krasnov et al, 1996) soil structure and content have also been shown to be important factors.…”
Section: Comparisons With Previous Studies Of Rodent Community Compossupporting
confidence: 52%
“…For rodent communities in general, vegetation cover and related productivity seem to be the main environmental determinants of community composition (Bian et al, 1994;Adler, 1995;Oguge, 1995). In the present study and other desert systems (south Bukhara desert, Uzbekistan, Shenbrot, 1992; Asian deserts, Shenbrot et al, 1994;Anix desert, China, Liu et al, 1994;Negev highlands, Israel, Krasnov et al, 1996) soil structure and content have also been shown to be important factors.…”
Section: Comparisons With Previous Studies Of Rodent Community Compossupporting
confidence: 52%
“…The feeding habits of Mastomys natalensis have been reported by several workers from a wide range of localities and habitats (e.g., Nandwa 1973, Field 1975, Perrin and Curtis 1980, Leirs et al 1989, Leirs 1995, Oguge 1995, Monadjem 1997, 1998. The aims of most of these studies have been to elucidate the importance of food on ecological factors, such as breeding and population dynamics.…”
Section: Introductionmentioning
confidence: 88%
“…In contrast, small mammal diversity tends to be lower in less diverse and open habitats (Oguge, 1995;Pearson et al, 2001). Thus, small mammal assessment is an important component of the study of forest ecosystems because they are indicators of habitat condition.…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%